Factors associated with reported modern contraceptive use among married men in Afghanistan - Catherine A. Packer; Sayed Haroon Rastagar; Mario Chen; Alissa Bernholc; Shafiqullah Hemat; Sediq Seddiqi; Ross McIntosh; Elizabeth Costenbader; Catherine S. Todd (BMC, 2020)
Abstract Background Afghanistan has high maternal and infant mortality which is in part driven by high fertility and low modern contraceptive use. Using modern contraceptive methods can reduce maternal and infant mortality, however there are several barriers to modern contraceptive use in Afghanistan. Married men have the potential to hinder or facilitate their wives' contraceptive use. Internally displaced persons (IDP), a growing population in Afghanistan, are rarely included in reproductive health research. We explored whether married men's, including IDPs', gender-related attitudes and other factors were associated with reported modern contraceptive use to inform programming to meet reproductive health needs of married couples. Methods Cross-sectional study using data from 885 married men determined to have contraceptive need in seven Afghan provinces. We explored associations between sociodemographic factors, IDP status, wives' involvement in household decision-making and men's attitudes towards intimate partner violence (IPV) with reported modern contraceptive use using logistic regression analysis. Results Most men (78%) had ≥2 children, 60% reported any formal education, and 30% reported being IDPs. Only 38% of married men and 24% of IDPs with contraceptive need reported using modern contraception with their wives. Most (80% overall, 63% of IDPs) reported their wives' involvement in some/all household decisions, while 47% overall and 57% of IDPs reported IPV was justified in one or more listed circumstances. In bivariate analysis, men responding that IPV was not justified in any listed circumstance were more likely and IDPs less likely to report modern contraceptive use. In multivariable analysis, involvement by wives in household decision-making (AOR 2.57; 95% CI: 1.51, 4.37), owning a radio and/or television (AOR 1.69; 95% CI: 1.10, 2.59), having more children, age, and province of interview were independently associated with reported modern contraceptive use, while IDP status was not. Conclusions Our findings reflect positive associations between wives' participation in household decisions and mass media exposure (television/radio ownership) with reported modern contraceptive use. Reproductive health initiatives engaging men to promote communication within couples and through mass media channels may further increase modern contraceptive use and advance Afghanistan's family planning goals. As fewer IDPs owned a radio/television, additional outreach methods should be tested for this group.